RURAL COLLEGE EFL LEARNERS’ BARRIERS IN WRITING A RESEARCH PAPER: A PHOTOVOICE PHENOMENOLOGICAL APPROACH - Heri Mudra (IAIN Syekh Nurjati Cirebon, 2023)
This current study aimed to investigate rural college EFL students’ experiences in dealing with English research paper writing and publication barriers. Five senior EFL students voluntarily participated in a photovoice phenomenological study. The data were collected through two methods, including semi-structured interviews and a photovoice. The students took some emotional photos to express their feeling on paper writing and publication barriers visually. The interviews encouraged them to describe their experiences and feelings through the photos. The data were analyzed by synchronizing each photo with its qualitative description. As for the results, it is noted that there were three main paper writing and publication barriers, including a lack of linguistic competence, being trapped with a journal template, and anxiety towards written corrective feedback. Each interview result was accomplished with emotional photos in several themes such as untidy pieces of paper, scenery, internet search, children’s toys, colourful pens, and empty box. The photos were also supported by qualitative remarks of each EFL student. In short, the photovoice helps to represent deep feelings on the research paper writing and publication barriers experienced by the EFL students.